2017
DOI: 10.1016/j.je.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and all-cause and cancer mortality: BioBank Japan cohort

Abstract: BackgroundStatins are the first-line agents used to treat patients with high serum low-density lipoprotein cholesterol levels, thus reducing the risk of death from arterial sclerotic cardiovascular disease; however, little is known about the effects of non-statin pharmacological interventions on mortality as well as about the potential protective effects of statin use against cancer death. This work aimed to compare all-cause and cancer mortality among patients with hyperlipidaemia who did and did not receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Kaplan-Meier survival curves also revealed no difference. This is in accordance with a recently published cohort study including 41,900 patients [ 46 ]. Since statins are immune-modulating [ 47 ], it is possible that symptoms are delayed and that patients using statins receive their diagnosis at a later stage and therefore have a lower survival rate.…”
Section: Discussionsupporting
confidence: 93%
“…Kaplan-Meier survival curves also revealed no difference. This is in accordance with a recently published cohort study including 41,900 patients [ 46 ]. Since statins are immune-modulating [ 47 ], it is possible that symptoms are delayed and that patients using statins receive their diagnosis at a later stage and therefore have a lower survival rate.…”
Section: Discussionsupporting
confidence: 93%
“…This finding implies that an elevated FFA level may be a potential biomarker for cancers. Some studies (Nayan et al 2017;Yokomichi et al 2017;Li et al 2019a, b) have found that statin use in cancer improves survival outcomes and increases overall survival. Our results can also explain why lipid-lowering therapy can improve clinical outcomes since cancer patients have elevated FFA levels even when serum TGs are normal.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been many epidemiologic studies and meta-analyses on the beneficial effect of statin on cancer incidence and mortality or survival. However, the results were conflicting on these associations [10][11][12]. In addition, some of these reported associations could be caused by biases.…”
Section: Introductionmentioning
confidence: 99%